(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In this article devoted to the phraseological analys of english and uzbek languages. In this, we tried to give an alternative version of phrases in uzbek and inglish languages. In this days inglishand uzbek idioms is really challanging to translate one to second. Also, it a bit difficult to find alternative phrases that make sens to each other research.